MICROFINANCE SERVICES AND POVERTY REDUCTION AMONG RURAL ENTREPRENEURS IN ANAMBRA STATE, SOUTHEAST NIGERIA - Ugochukwu Okorie, Nkume; Osita-Njoku , Agnes; Nwabuaku Kanu, Winifred (African Journal of Social and Behavioural Sciences, 2026)
This study examined the association between microfinance services and poverty reduction indicators among rural entrepreneurs in Anambra State, Southeast Nigeria. Specifically, the research investigated how access to microcredit, savings services, and financial literacy training relates to income levels, business growth, and asset ownership. A descriptive survey design was adopted, with a structured questionnaire administered to 320 rural entrepreneurs selected through multistage sampling across six local government areas representing the three senatorial districts. Data were analyzed using descriptive statistics (mean scores and standard deviation), while hypotheses were tested using Multivariate Analysis of Covariance (MANCOVA). Findings revealed that access to microcredit was associated with higher income levels (mean = 3.44, SD = 0.78), with MANCOVA showing significant relationship (Wilks’ Λ = 0.763, F = 6.295, p < 0.001). Savings services were associated with business growth (mean = 3.36, SD = 0.84; Wilks’ Λ = 0.815, F = 5.017, p < 0.001). Financial literacy training was associated with asset ownership (mean = 3.41, SD = 0.77; Wilks’ Λ = 0.802, F = 5.588, p < 0.001). The study concluded that microfinance services are positively associated with poverty alleviation and business sustainability indicators. It recommended increased access to microcredit, incentivized savings schemes, and localized financial literacy programs.